Evaluating the influencing factors of food imports within belt and road initiatives (BRI) countries: An economic threshold model approach - Wang, Yameng; Sarkar, Apurbo (Frontiers in Sustainable Food Systems, 2022)
International food chains and trade usually support many vulnerable and food-insecure developing countries to ensure stable access to food and sufficient resources to maintain and enhance economic growth. However, the smooth transition of uninterrupted food trade and supply is one of the major concerns for almost every country. Based on the economic threshold model grouping tactics, the study evaluates the influencing factors of global food imports and how different countries foster food imports in different conditions. The empirical data has been comprised of panel data from 91 countries along the “Belt and Road” for the last 21 years. The results show that: (i) Population size and arable land endowment have single and double threshold effects on food imports. (ii) Economic development has different effects on the food imports of each group of countries. It has an inverted U-shaped relationship with countries with large populations and high arable land endowments and a “U-shaped relationship” with countries with low arable land endowments. There is a linear relationship between the food imports of countries with small populations and medium arable land endowments, and there is no significant impact on food imports of countries with large populations and medium arable land endowments. (iii) The impact of infrastructure, technological progress, food stocks, and industrial structure on food imports varies from country to country, but tariff policies have no significant impact on food imports. All member countries should utilize the platform of “Belt and Road Initiatives” to capture the resource endowment and exchange associated science and technology of food production, processing, transport, and storage. Food productivity and self-dependency on food should also be increased.